Planning for an Anaerobic Baffled Reactor as a Waste Water Treatment Unit at the Tahfidzul Qur'an Bambu Kuning Girls' Dormitory, Tanggul Kulon Village, Tanggul District, Jember Regency - Islam, Muhammad Fikrul; Al-Rosyid, Latifa Mirzatika; Alihudien, Arief (International Applied Science, 2023)
The Tahfidzul Qur'an Bambu Kuning girls' dormitory is an Islamic boarding school-based educational foundation located in Tanggul Kulon Village, Tanggul District, Jember Regency. The maximum number of dormitory residents uses calculations of the space capacity in the building and the development plan for the Islamic boarding school. Based on this approach, the maximum number of boarding school residents is 320 people. So if the occupants meet the maximum capacity, the waste that will be produced is 61.44 m3/day. The handling of domestic waste (blackwater and greywater) at the Tahfidzul Qur'an Bambu Kuning girls' dormitory is still processed using a septic tank which directly absorbs into the ground and there has been no draining activity so far. This has the potential for environmental pollution, which causes the potential to increase. suffer from disease. Therefore, it is necessary to make efforts to improve sanitation, namely planning a domestic wastewater treatment plant with an Anaerobic Baffled Reactor (ABR). The planned ABR has 3 compartments with total dimensions of length, width and depth of 12.3 meters, 6.12 meters and 2.5 meters. Construction with the ABR unit produces low concentrations of BOD, COD, TSS, oil and fat, and total coliform, respectively 6.82 mg/L, 17.5 mg/L, 7.87 mg/L, 1.46 mg/ L, and 300 mg/L which meets the quality standards set by the Minister of Environment and Forestry Regulation No. 68 of 2016 concerning domestic wastewater quality.